2021
DOI: 10.1186/s12933-021-01267-w
|View full text |Cite
|
Sign up to set email alerts
|

PAR-4/Ca2+-calpain pathway activation stimulates platelet-derived microparticles in hyperglycemic type 2 diabetes

Abstract: Background Patients with type 2 diabetes (T2DM) have a prothrombotic state that needs to be fully clarified; microparticles (MPs) have emerged as mediators and markers of this condition. Thus, we investigate, in vivo, in T2DM either with good (HbA1c ≤ 7.0%; GGC) or poor (HbA1c > 7.0%; PGC) glycemic control, the circulating levels of MPs, and in vitro, the molecular pathways involved in the release of MPs from platelets (PMP) and tested their pro-inflammatory effects on THP-1 transformed macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…An altered platelet membrane ultrastructure with apoptotic morphology and membrane has been reported in diabetic patents [ 43 ], along with enhanced platelet-derived microparticle (PMP) formation [ 44 ]. It has been recently demonstrated that under chronic hyperglycemia, protease-activated receptor 4 promotes release of PMPs through a Ca 2+ -calpain dependent mechanism [ 45 ]. Fibrin clots formed in the presence of microparticles have been shown to be less susceptible to tPA-induced fibrinolysis in healthy subjects [ 46 ], and this can be most likely extrapolated to diabetic patients.…”
Section: Mechanisms Of Hypofibrinolysis In T2dmmentioning
confidence: 99%
“…An altered platelet membrane ultrastructure with apoptotic morphology and membrane has been reported in diabetic patents [ 43 ], along with enhanced platelet-derived microparticle (PMP) formation [ 44 ]. It has been recently demonstrated that under chronic hyperglycemia, protease-activated receptor 4 promotes release of PMPs through a Ca 2+ -calpain dependent mechanism [ 45 ]. Fibrin clots formed in the presence of microparticles have been shown to be less susceptible to tPA-induced fibrinolysis in healthy subjects [ 46 ], and this can be most likely extrapolated to diabetic patients.…”
Section: Mechanisms Of Hypofibrinolysis In T2dmmentioning
confidence: 99%
“…Gianella et al [ 167 ] demonstrated for the first time that PAR-4 as a mediator of platelet activation promoted the release of activated PMVs through a calcium calpain-dependent mechanism and the expression of PAR-4 is upregulated by chronic hyperglycemia in poorly controlled (HbA1c > 7.0%) T2DM patients. PAR-4 also had a pro-inflammatory effect on the release of IL-6 from macrophages treated with platelets from poorly controlled patients.…”
Section: Role Of Platelet In Pathogenesis Of Dkdmentioning
confidence: 99%
“…Exosomal calpain 2 can cleave the ectodomain of the insulin receptor and thus impair insulin action, providing a credible link between calpain 2, exosomes, and T2D etiology 248 . Moreover, activation of calpain 1 and 2 contributes to accelerated atherothrombosis development in T2D by regulating different substrates in platelets and ECs 177 - 181 . Since MVs loaded with elevated calpain 1 can be delivered to ECs and induce vascular inflammation 180 , 181 , MVs might contribute to the phenotypes mentioned above.…”
Section: Ev Biogenesis Machinery In Dm and Diabetic Complicationsmentioning
confidence: 99%
“…Moreover, activation of calpain 1 and 2 contributes to accelerated atherothrombosis development in T2D by regulating different substrates in platelets and ECs 177 - 181 . Since MVs loaded with elevated calpain 1 can be delivered to ECs and induce vascular inflammation 180 , 181 , MVs might contribute to the phenotypes mentioned above.…”
Section: Ev Biogenesis Machinery In Dm and Diabetic Complicationsmentioning
confidence: 99%